A review of the systematics of the genus Bradypodion (Sauria: Chamaeleonidae), with the description of two new genera - Tilbury, Colin R.; Tolley, Krystal A.; Branch, William R. (Zootaxa, 2006)
The taxonomic history and composition of the genus Bradypodion as construed by Klaver & Böhme (1986) and new morphological and molecular data relevant to the taxonomy of the group is reviewed. The combined evidence strongly supports a formal rearrangement of the group into three distinct genera. Bradypodion, type species Chamaeleo pumilus Daudin 1802, is retained for the southern African species. Two new genera are erected to accommodate additional well-diagnosed clades within central and east African species previously referred to Bradypodion. Species of the “fischeri complex” are assigned to Kinyongia gen. nova, whilst the endemic Mulanje chameleon is placed in the monotypic genus Nadzikambia gen. nova.